Regulation of the NLRP3 Inflammasome by Post-Translational Modifications and Small Molecules - Seok, Jin Kyung; Kang, Han Chang; Cho, Yong-Yeon; Lee, Hye Suk; Lee, Joo Young (Frontiers in Immunology, 2021)
Inflammation is a host protection mechanism that eliminates invasive pathogens from the body. However, chronic inflammation, which occurs repeatedly and continuously over a long period, can directly damage tissues and cause various inflammatory and autoimmune diseases. Pattern recognition receptors (PRRs) respond to exogenous infectious agents called pathogen-associated molecular patterns and endogenous danger signals called danger-associated molecular patterns. Among PRRs, recent advancements in studies of the NOD-, LRR- and pyrin domain-containing protein 3 (NLRP3) inflammasome have established its significant contribution to the pathology of various inflammatory diseases, including metabolic disorders, immune diseases, cardiovascular diseases, and cancer. The regulation of NLRP3 activation is now considered to be important for the development of potential therapeutic strategies. To this end, there is a need to elucidate the regulatory mechanism of NLRP3 inflammasome activation by multiple signaling pathways, post-translational modifications, and cellular organelles. In this review, we discuss the intracellular signaling events, post-translational modifications, small molecules, and phytochemicals participating in the regulation of NLRP3 inflammasome activation. Understanding how intracellular events and small molecule inhibitors regulate NLRP3 inflammasome activation will provide crucial information for elucidating the associated host defense mechanism and the development of efficient therapeutic strategies for chronic diseases.